Industrial robot performance simulation using a fuzzy logic/neural network controller - Tin, Aung Win. (2009)
The objectives of this thesis are to study the learning capability of the fuzzy/neural controller, to perform simulation of the proposed controller and to investigate the performance for an industrial robotic manipulator SCARA (Adept One). The contributions of the thesis are (1) interpretation of the knowledge learnt by the fuzzy/neural controller, and (2) the effectiveness of the controller used in controlling a dynamic system (industrial robot SCARA).